PENGEMBANGAN MAJALAH ELEKTRONIK BERBASIS KONTEKSTUAL DALAM MUATAN PELAJARAN IPS KELAS V SEKOLAH DASAR - Nadiah Septiana; Nidya Chandra Muji Utami; Yustia Suntari (Universitas Negeri Surabaya, 2023)
This study aims to develop contextual based e-magazine on the content in social studies lesson class V elementary school. The method used is the Research and Development (RnD) with the development process using the model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). However, due to the Covid-19 pandemic this research is only up to the development phase. Data collection techniques used are observation, interview and questionnaire. Respondents in this research are one material expert lecturer, one media expert lecturer, one linguist lecturer, three 5th graders of elementary school for one to one phase, and twelve students for small group phases. The results of the feasibility of 1) Media expert validation obtained a score of 96,15%, 2) Material expert validation obtained a score of 93,75%, 3) Linguist validation obtained a score of 85%. Based on the results of the validation of the experts, overall a score of 92,4% was obtained in the very good category. The test to 5th graders of elementary school is resulting in average score of 93,33% for one-to-one phase and 96,67% for small group phase which was included in the very good category so that the product was declared suitable for use.